Investigating the Impact of Açai (Euterpe oleracea) on Lipid Profile: A Comprehensive Systematic Review and Meta-Analysis - Candeloro, Bruno Moreira [UNESP]; Bitencourt, Túlio H. B. [UNESP]; Elias, Sergio F. R. [UNESP]; Rauli, Maria Clara [UNESP]; Brandão, Isabela B. [UNESP]; Barbalho, Sandra Maria; Garner, David M.; Raimundo, Rodrigo D.; Porto, Andrey A. [UNESP]; Valenti, Vitor E. [UNESP] (Wiley, 2025)
Conditions such as obesity and cardiovascular diseases represent significant global public health challenges, driven by their increasing prevalence and profound effects on morbidity and mortality. Dyslipidemia, defined by abnormal lipid concentrations, performs a pivotal role in the onset of cardiovascular diseases, especially atherosclerosis. Dietary strategies and other nonpharmacological interventions are crucial for the management of dyslipidemia. Açaí (Euterpe oleracea), a fruit native to the Amazon, is recognised for its antioxidant properties and potential impact on lipid metabolism. This systematic review and meta-analysis aimed to assess the impact of açaí consumption on lipid profile markers. A systematic search was performed across several databases, including MEDLINE/PubMed, EMBASE, Web of Science and Scopus. We included non-randomised, randomised, no blind, blind and control trials involving adult participants who received açaí in any form. The outcome measures included triglycerides, total cholesterol, LDL-c and HDL-c. The screening of studies and data extraction were independently conducted by four reviewers. The risk of bias was evaluated using the Cochrane Risk of Bias tool, and meta-analyses were completed where applicable. Out of 188 identified studies, 8 met the inclusion criteria. Meta-analysis of 411 participants displayed no significant effect of açaí on LDL-c (MD = 6.06 mg/dL 95% CI: −0.03, 12.48, p = 0.06), HDL-c (MD = 0.30 mg/dL 95% CI: −1.54, 2.13, p = 0.75), total cholesterol (MD = 2.94 mg/dL 95% CI: −6.44, 12.31, p = 0.54) and triglycerides (MD = 2.05 mg/dL 95% CI: 1.79, 2.28, p = 0.59). Additionally, açaí consumption was related to a significant reduction in total lipids (MD = −9.80 g, 95% CI: −13.94 to −5.66, p < 0.001). GRADE evaluation pointed to low/very low certainty of evidence. Açaí consumption may lessen total lipid levels, but no significant effect was noted for cholesterol parameters and triglycerides. Further trials with more demanding research methodologies are required to clarify the effects of açaí on lipid profiles. Trial Registration: CRD42024549531.
Keywords: açai; cardiovascular diseases; dyslipidemia; Euterpe oleracea; lipid profile